«Geopolitical Challenge» to the Global Urban Research Boom - N. A. Sluka (Vestnik MGIMO-Universiteta)
Book review: Okunev I.Y. Capitals in the Mirror of Critical Geopolitics. Monograph. 2-e Izd., revised and enlarged. M.: Izdatel'stvo "Aspekt Press", 2020. 272 p.